Concussions in the National Basketball Association: Analysis of Incidence, Return to Play, and Performance From 1999 to 2018. Issue 6 (27th June 2019) - Patel, Bhavik H.; Okoroha, Kelechi R.; Jildeh, Toufic R.; Lu, Yining; Idarraga, Alexander J.; Nwachukwu, Benedict U.; Shen, Sarek A.; Forsythe, Brian
Background: The effect of concussions on professional athletes has been investigated in many sports. However, few studies have evaluated concussions in National Basketball Association (NBA) players. Hypothesis: We hypothesized that concussion incidence has increased, yet the return-to-play (RTP) rate will remain high following the institution of the NBA concussion policy (NBACP). We also hypothesized that the incidence of repeat concussions will be similar to first occurrences and that player performance and game availability will not be significantly affected by sustaining a concussion. Study Design: Descriptive epidemiology study. Methods: Publicly available records were searched to identify all concussions from NBA seasons 1999-2000 to 2017-2018. Player demographics and information regarding career history were tabulated. Incidence of concussion and RTP timing were evaluated before and after institution of the NBACP (2011). Minutes per game and game score per minute were evaluated pre- versus postconcussion. Player availability and performance were also compared with an age-, body mass index–, position-, and experience-matched control group of players who did not sustain a concussion. Results: A total of 189 concussions were reported in the NBA from 1999 to 2018, with a mean ± SD incidence of 9.7 ± 7.3 concussions per season. Following implementation of the NBACP, incidence significantly increased from 5.7 ± 2.8 to 16.7 ± 7.5 concussions per season ( P = .007). All players returned to play following first-time concussion after missing 7.7 ± 8.6 days and 3.5 ± 4.1 games. RTP time was not significantly different after implementation of the NBACP (games missed, P = .24; days missed, P = .27), and there was no difference in concussion-free time interval ( P = .29). Game score per minute and minutes per game were not significantly affected by sustaining a concussion (both P > .05). Conclusion: Concussion incidence in NBA players is approximately 17 instances per season since the 2011 institution of a league-wide concussion policy. The number of reported concussions significantly increased following the policy, in line with trends seen in other professional sports leagues. Players have retained a high rate of RTP after 3 to 4 missed games. Player performance and availability are not affected by sustaining a concussion following successful RTP.